Corporate storytelling and the idea of Latin America - Mariana I. Paludi; Jean Helms Mills; Albert J. Mills (RAE: Revista de Administração de Empresas)
The aim of this article is contributing to a great variety of theoretical perspectives and empirical settings to generate cumulative evidence about the influence of historical legacies and organizational ability for managing the past. In a continuation of critical perspectives that challenges the dominance of Anglo-Saxon onto-epistemologies in management and organization studies (MOS), we conducted an empirical study on a multinational airline company whose past successes depended on the North/South, Anglo/Latin American borderlands. We analyzed the grand narratives of Pan American Airways’ (PAA) corporate archival material to determine its dominant discourses about people from Latin America. Based on the three themes of politics, economics, and culture, we present three grand narratives, or official stories, that we argue summaries PAA storytelling about Latin America between 1927 and 1960. Following decolonial feminism, we aim to recontextualize the past and the hegemonic storytelling embedded in PAA’s grand narratives.